1976
DOI: 10.1213/00000539-197603000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Choice Between Tracheostomy and Prolonged Translaryngeal Intubation in Acute Respiratory Failure

Abstract: One of the problems of prolonged ventilatory therapy in acute respiratory failure (ARF) is the need to choose between tracheostomy after 48 to 72 hours of translaryngeal (TL) tracheal intubation or the continuous use of the TL tube for a period of 10 days. Too often the choice has been based on retrospective studies or personal preference. To investigate this problem prospectively, 52 adults in ARF were divided sequentially into 2 groups on their 3rd day of TL intubation. Patients in group I (G-I) retained the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Although prolonged translaryngeal intubation causes tissue trauma, promotes bacterial translocation and infection, and usually requires sedation to reduce patient discomfort, there is little evidence to guide optimal timing for a tracheostomy, in part because of the methodological diversity in the 15 studies and one systematic review which have been conducted in this area (table 8) [109,160,[166][167][168][169][172][173][174][175][176][177][178][179][180][181]. Only eight of these studies are randomised controlled trials, four of which have been published since 1997 [168,169,172,173].…”
Section: Timing Of Tracheostomymentioning
confidence: 99%
“…Although prolonged translaryngeal intubation causes tissue trauma, promotes bacterial translocation and infection, and usually requires sedation to reduce patient discomfort, there is little evidence to guide optimal timing for a tracheostomy, in part because of the methodological diversity in the 15 studies and one systematic review which have been conducted in this area (table 8) [109,160,[166][167][168][169][172][173][174][175][176][177][178][179][180][181]. Only eight of these studies are randomised controlled trials, four of which have been published since 1997 [168,169,172,173].…”
Section: Timing Of Tracheostomymentioning
confidence: 99%
“…a1., 8 and Stauffer et al9 compared translaryngeal intubation with tracheostomy in critically ill patients. Outcome analyses centered solely on the complications of tracheostomy and risk of tracheal stenosis.…”
Section: /6/22940mentioning
confidence: 99%
“…For all other patients, the decision regarding the timing of tracheostomy was left to daily assessment and physician preference. Such practice was based on earlier reports showing high tracheal stenosis rates with tracheostomy as compared with endotracheal intubation [5,6]. For example, one study reported in 1981 [6] found an incidence of tracheal stenosis after tracheostomy of 65%, as compared with 19% after endotracheal intubation.…”
Section: Introductionmentioning
confidence: 99%